Profilaksis Pasca Paparan Virus HIV pada Petugas Kesehatan - Karjadi, Teguh Harjono (UI Scholars Hub, 2023)
Health workers (HCWs) are prone to get infected by HIV infection when carrying out their duties. The injuries can be caused by needle sticks, sharp objects (scalpels, lancets, or other) that have been exposed to body fluids or splashes of body fluids onto the body’s mucosa (eyes, nose, mouth) and non-intact skin have the potential to transmit the HIV infection. Post-exposure transmission due to contamination of body fluids to health workers can be prevented by providing post-exposure prophylaxis therapy. Post-exposure prophylaxis (PEP) is given as soon as possible and no later than 72 hours after exposure. Prophylaxis is given to HCWs who are significantly exposed using three antiretroviral drugs. In Indonesia, for adolescents and adults ≥ 10 years old, the main choice is Tenofovir (TDF) + Lamivudine (3TC) + Dolutegravir (DTG). Simultaneously with the administration of ARV drugs, counseling is also carried out regarding side effects of ARV, medication adherence, drug interactions, the possibility of seroconversion, and if necessary, management of anxiety that may arise. ARVs will be given for 28 days. After being given post-exposure prophylactic therapy, monitoring for side effects of ARV drugs must be carried out which are given in the 2nd and 4th week. Re-examination of HIV testing to see the effectiveness of treatment was carried out at 12 weeks and 6 months after exposure. Keywords: HIV infection, PEP of HIV